2012
DOI: 10.1038/modpathol.2011.218
|View full text |Cite
|
Sign up to set email alerts
|

Loss of keratin 13 in oral carcinoma in situ: a comparative study of protein and gene expression levels using paraffin sections

Abstract: Immunohistochemical loss of keratin (K)13 is one of the most valuable diagnostic criteria for discriminating carcinoma in situ (CIS) from non-malignancies in the oral mucosa while K13 is stably immunolocalized in the prickle cells of normal oral epithelium. To elucidate the molecular mechanism for the loss of K13, we compared the immunohistochemical profiles for K13 and K16 which is not expressed in normal epithelia, but instead enhanced in CIS, with their mRNA levels by in-situ hybridization in formalin-fixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 20 publications
3
44
0
4
Order By: Relevance
“…Ohkura et al [18] reported that CK13 expression levels were lower in oral squamous cell carcinoma and severe epithelial dysplasia than in mild and moderate epithelial dysplasia, and several additional studies have since reported that CK13 expression decreases with increasing severity of epithelial dysplasia [12,13,19]. The mechanism of CK13 expression has not yet been fully elucidated, but Ida-Yonemochi et al [15] suggested that K13 might be posttranscriptionally regulated by repression of gene translation in oral keratinocytes. A similar relationship between CK13 expression and malignant potential has been reported in uterine cervical [23] and oesophageal epithelia [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ohkura et al [18] reported that CK13 expression levels were lower in oral squamous cell carcinoma and severe epithelial dysplasia than in mild and moderate epithelial dysplasia, and several additional studies have since reported that CK13 expression decreases with increasing severity of epithelial dysplasia [12,13,19]. The mechanism of CK13 expression has not yet been fully elucidated, but Ida-Yonemochi et al [15] suggested that K13 might be posttranscriptionally regulated by repression of gene translation in oral keratinocytes. A similar relationship between CK13 expression and malignant potential has been reported in uterine cervical [23] and oesophageal epithelia [24].…”
Section: Discussionmentioning
confidence: 99%
“…A multitude of studies have found significant relationships between malignancy and the expression levels of CK13 and CK17, indicating that combined assessment of CK13 and CK17 expression status might be a highly reliable diagnostic test to identify malignant transformation of oral epithelial dysplasia and oral squamous cell carcinoma [11,12,13,14,15,16,17,18,19,20]. However, it was previously unknown whether the expression status of CK13 or CK17 correlates with the morphological signs of atypia in superficial oral squamous cells collected by oral exfoliative cytology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research shows that long-term use of alcohol-containing mouthwashes may lead to rapid atrophy of different types of papillae, disturbance of metabolic enzymes in oral cavity, and vascular insufficiency [25]. In addition, evidence indicates that regular alcohol consumption induces sever changes of oral mucosal cells due to substantial alteration of epidermal growth factor receptors (EGFR) and loss of keratin 13 proteins [26][27][28]. This clearly implies that alcohol showed a higher capacity to eliminate the lipid components of the cell barriers in the oral cavity, which surround the cellular granules at the epithelial spinous layer [6].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokeratin is a helpful diagnostic marker for evaluation of cellular differentiation in tumors (4), and cytokeratins 13 and 19 in particular are useful for diagnosis or biological characterization of oral precancerous lesions or carcinomas in situ in squamous epithelium (5,6). However, the distribution of cytokeratin differs among the various types of oral mucosa, such as those overlying the tongue and the gingiva, and thus shows a degree of heterogeneity.…”
Section: Introductionmentioning
confidence: 99%